School bag needs of selected students with scoliosis - Malsi, Lauran Alyssa B.; Lumawig, Maria Josephine T. (Quezon City College of Home Economics, University of the Philippines, 2015)
ABSTRACT As of late, there is no comprehensive study on the specific bag features that aid scoliotic students. Scoliotic students face physical challenges. They can greatly benefit from bag designs with features that support the spine and cater to their specific issues so that they can do school activities with ease. This study aimed to recommend a school bag design for scoliotic students by describing and analysing their physical challenges, needs, and issues in relation to the use of school bags. The researcher surveyed material and construction solutions devised by athletic, travel, and lifestyle-tech bag manufacturers and found that these can be used to solve scoliotic needs. The researcher surveyed a sample of 42 purposively selected individuals with scoliosis aged 16 to 28 years old with varying Cobb Angle degrees. A braced UP freshman was chosen to undergo extensive personal interview and figure analysis. Focus group discussions were also conducted to identify the needs of scoliotic students. The researcher chose to design a backpack as this was the most used type among respondents. It is also built with an internal frame to support the respondents' average bag weight of 13.78 pounds. The most cited items brought daily were notebooks, laptops, and other gadgets so compartments were placed to organise these for ergonomic loading. The bag is also fitted with back sleeves for customised padding and a roll-out seating pad that doubles as lumbar support. The material recommended was a ripstop fabric made of corespun Dyneema-Bamboo fiber which has excellent abrasion resistance, breathability, and antibacterial properties to protect the bag from being punctured by brace accessories and minimize perspiration. The researcher recommends further studies on specific control groups of scoliotic students as well as testing and evaluation of the recommended design.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Bags -- Design